A mixed methods study of physical activity and quality of life in adolescents with Turner syndrome. Issue 2 (8th December 2019) - Thompson, Talia; Zieba, Brianna; Howell, Susan; Karakash, William; Davis, Shanlee
Abstract: Women with Turner syndrome (TS) have a high morbidity from both medical and psychological conditions with a negative impact on quality of life (QoL). Physical activity is a modifiable behavior shown to reduce risk for these chronic medical and mental health conditions and enhance QoL in other populations. Limited research suggests that adolescents and women with TS are less likely to engage in or enjoy physical activity than peers. This mixed methods study aimed to document physical activity levels in a sample of youth with TS and explore how factors unique to TS contribute to and are affected by physical activity. A cross‐sectional sample of 21 girls (12–21 years) with TS and their parents ( n = 21) completed standardized questionnaires to quantify habitual physical activity (3‐day physical activity recall) and QoL (PROMIS) and participated in individual interviews focused on their experience with physical activity. Quantitative and qualitative results were synthesized using a phenomenological mixed methods approach. Results indicate that our sample engaged in less physical activity than peers and only 19% met recommendations for 1 hr per day of moderate‐to‐vigorous physical activity. Parents reported significant problems with peer relationships and psychological stress, and peer relationships scores correlated with physical activity. Reported barriers to physical activity included physical and psychosocial complications related to TS as well as unique developmental considerations specific to adolescence. Quantitative and qualitative results supported that structured fitness options embedded into routines enhanced activity levels. Results were compiled into specific recommendations for clinical care and areas of future research.